Latest advances in protein-recovery technologies from agricultural waste - Mohd Yusree, Farhana Iylia Fatinee; Peter, Angela Paul; Mohd Nor, Mohd Zuhair; Show, Pau Loke; Mokhtar, Mohd Noriznan (MDPI AG, 2021)
In recent years, downstream bioprocessing industries are venturing into less tedious, simple, and high-efficiency separation by implementing advanced purification and extraction methods. This review discusses the separation of proteins, with the main focus on amylase as an enzyme from agricultural waste using conventional and advanced techniques of extraction and purification via a liquid biphasic system (LBS). In comparison to other methods, such as membrane extraction, precipitation, ultrasonication, and chromatography, the LBS stands out as an efficient, cost-effective, and adaptable developing method for protein recovery. The two-phase separation method can be water-soluble polymers, or polymer and salt, or alcohol and salt, which is a simpler and lower-cost method that can be used at a larger purification scale. The comparison of different approaches in LBS for amylase purification from agricultural waste is also included. Current technology has evolved from a simple LBS into microwave-assisted LBS, liquid biphasic flotation (LBF), thermoseparation (TMP), three-phase partitioning (TPP), ultrasound-assisted LBS, and electrically assisted LBS. pH, time, temperature, and concentration are some of the significant research parameters considered in the review of advanced techniques.